2016
DOI: 10.21037/tau.2016.05.03
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiology of delayed ejaculation

Abstract: Delayed ejaculation (DE) is probably least studied, and least understood of male sexual dysfunctions, with an estimated prevalence of 1–4% of the male population. Pathophysiology of DE is multifactorial and including psychosexual-behavioral and cultural factors, disruption of ejaculatory apparatus, central and peripheral neurotransmitters, hormonal or neurochemical ejaculatory control and psychosocial factors. Although knowledge of the physiology of the DE has increased in the last two decade, our understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 94 publications
0
12
0
5
Order By: Relevance
“…reported that patients with primary DE have penile shaft rather than glans hyposensitivity, though it is not stated if the patients have unusual masturbation. Through unusual masturbation, patients with DE may develop the autosexual patterns that produce different types of orgasm from what they experience with a partner 15…”
Section: Commentsmentioning
confidence: 99%
“…reported that patients with primary DE have penile shaft rather than glans hyposensitivity, though it is not stated if the patients have unusual masturbation. Through unusual masturbation, patients with DE may develop the autosexual patterns that produce different types of orgasm from what they experience with a partner 15…”
Section: Commentsmentioning
confidence: 99%
“…Erectile dysfunction, PE, and painful ejaculation are the leading sexual symptoms of urogenital infections. However, there is no definitive evidence of the actual frequency of DE/AE in patients with urogenital infections or of the true pathophysiological role of these inflammatory disorders in ejaculatory delay [ 75 ]. Urogenital infections can produce scarring and obstruction anywhere in the male reproductive tract.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…DE, anejaculation, and anorgasmia are among the least common and least understood male sexual health dysfunctions. The estimated prevalence of DE is 1–4% of the male population ( 99 ). These disorders are thought of as related entities on one end of a spectrum, with PE on the other end of the spectrum ( 100 ).…”
Section: Disorders Of Ejaculationmentioning
confidence: 99%
“…Anatomically, damage to pelvic nerves (following prostatectomy, RPLND, TURP, bladder neck incision, or other colorectal or pelvic surgery), and spinal cord injuries may also cause DE ( 17 , 99 , 100 , 105 , 113 , 114 ).…”
Section: Disorders Of Ejaculationmentioning
confidence: 99%